EFEKTIVITAS PENGGUNAAN AI DALAM MENINGKATKAN KETERAMPILAN MENGAJAR CALON GURU: SUATU TINJAUAN PUSTAKA SISTEMATIS - Setiawan, Angga (Universitas Negeri Surabaya, 2026)
Background/Purpose: The rapid emergence of Artificial Intelligence (AI) necessitates an investigation into its impact on pre-service teacher (PST) competence. This systematic literature review (SLR) investigates AI's effectiveness in enhancing PSTs' teaching skills and professional competence. Methodology: Following PRISMA guidelines, a comprehensive database search yielded 68 initial studies, with 17 selected for synthesis. The analysis focused on AI tools, targeted teaching skills, and competence development, mediating factors like learning motivation (LM) and perceived usefulness (PU). Findings: AI interventions significantly enhance various teaching skills. AI-driven simulations and conversational agents improve responsive teaching, instructional dialogue quality , and nonverbal skills. AI-supported learning positively impacts Pedagogical Content Knowledge (PCK), TPACK , and deepens reflective patterns. The benefits are strongly mediated by enhanced LM and PU. Conclusion: AI implementation is a scalable and ethical mechanism to bridge the theory-practice gap, significantly developing PSTs' teaching expertise. A focused approach integrating TPACK and PCK is crucial to maximize pedagogical benefits.